Reversible Protonation of Porphyrinic Metal‐Organic Frameworks Embedded in Nanoporous Polydimethylsiloxane for Colorimetric Sensing. Issue 10 (18th March 2021) - Sousaraei, Ahmad; Queirós, Carla; Moscoso, Francisco G.; Silva, Ana M. G.; Lopes‐Costa, Tânia; Pedrosa, José M.; Cunha‐Silva, Luís; Cabanillas‐Gonzalez, Juan
Abstract: A fast and reversible switch between the neutral and protonated porphyrin forms inside a pliable porphyrinic metal–organic framework (MOF), enabled by reversible structural deformation is unveiled. This phenomenon is applied for the development of MOF‐polymer porous composites to reveal biogenic amines by color changes. Abstract : The authors report on robust and reversible colorimetric sensors based on composites of porphyrinic‐MOFs and PDMS fabricated with a solvent‐free method. The colorimetric sensor is sensitive to biogenic amines released from organic decomposition showing a fast and efficient green‐to‐brown color change. They demonstrate that the hollow and flexible structure of the porphyrinic MOF is crucial for the observed optical changes.